Halalan toyyiban supply chain of the food industry / Emi Normalina Omar, Harlina Suzana Jaafar & Muhamad Rahimi Osman - Omar, Emi Normalina; Jaafar, Harlina Suzana; Osman, Muhamad Rahimi (Faculty of Business and Management, 2013)
In the era of globalization, halalan toyyiban supply chain (HTSC) is a contemporary approach to the global market. This study explores the supply chain process and discloses the practicalities in the production of halal chicken meat. The research focus on storage of the poultry, which covers from farm to customer, in particular the identification of the HTSC critical control points along the process of the supply chain. The research also categorizes the food supply chain process into three phases i.e. preslaughtering, slaughtering and post-slaughtering. This study emphasizes on chicken meat, which is two-third of the meat sales in Malaysia and Klang Valley as the case study. Interviews were used in identifying the halal/halalan and toyyib/toyyiban issues, and control points along in storage, which are frequently interrelated